Post-neoliberal developmental regimes in Latin America: Argentina under Cristina Fernandez de Kirchner. Issue 3 (3rd May 2016) - Wylde, Christopher
ABSTRACT: This article seeks to analyse the concept of post-neoliberalism through state theory, grounded in an understanding of the state as a historical institution influenced by both domestic and international forces. This theoretical exercise is complemented with a discussion of contemporary Argentina under the Presidency of Cristina Fernandez de Kirchner, showing that focus on a 'developmental regime tripod' reveals underlying tensions in the post-neoliberal model as a result of a desire to 'deepen that model' combined with shifts in the nature of international political economy in the wake of the global financial crisis.